1986
DOI: 10.1038/320077a0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of human lipocortin, a phospholipase A2 inhibitor with potential anti-inflammatory activity

Abstract: The anti-inflammatory action of glucocorticoids has been attributed to the induction of a group of phospholipase A2 inhibitory proteins, collectively called lipocortin. These proteins are thought to control the biosynthesis of the potent mediators of inflammation, prostaglandins and leukotrienes, by inhibiting the release of their common precursor, arachidonic acid, a process that requires phospholipase A2 hydrolysis of phospholipids. Lipocortin-like proteins have been isolated from various cell types, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
286
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 658 publications
(293 citation statements)
references
References 18 publications
5
286
0
Order By: Relevance
“…Although it is synthesized as a soluble cytoplasmic protein (Wallner et al, 1986), p35 is secreted (Christmas et al, 1991) and has extracellular anti-inflammatory and endocrine activities (Cirino et al, 1987;Pihoker et al, 1991). In rat embryos we have shown that p35 is expressed transiently at high levels in very restricted cell populations, a pattern characteristic of regulatory substances (McKanna and Cohen, 1989).…”
Section: Introductionmentioning
confidence: 73%
“…Although it is synthesized as a soluble cytoplasmic protein (Wallner et al, 1986), p35 is secreted (Christmas et al, 1991) and has extracellular anti-inflammatory and endocrine activities (Cirino et al, 1987;Pihoker et al, 1991). In rat embryos we have shown that p35 is expressed transiently at high levels in very restricted cell populations, a pattern characteristic of regulatory substances (McKanna and Cohen, 1989).…”
Section: Introductionmentioning
confidence: 73%
“…28 This effect takes two hours to develop. [29][30][31][32] It is possible that a cortisol depressant effect may have influenced the findings of Stanley et al, as at that sample time a neutrophilia was present in their patients. After 90 rain of anaesthesia and surgery, our patients did not show any alterations in total white counts compared with preoperative levels in any group probably due to a shorter duration of anaesthesia prior to the commencement of surgery in all groups.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis IS supported by the fact that hpocortm rnRNA Inductton has been detected m rat macrophages [44] and thymoeytes [21] after m vwo admmlstration of DEX. In addition.…”
Section: By Glucocortlcoldsmentioning
confidence: 93%